Relationship Between NM Data and Radiation Dose at Aviation Altitudes During GLE Events - N. Larsen; A. Mishev (Space Weather)
Abstract Ground‐level enhancements (GLEs) are sporadic events that signal the arrival of high fluxes of solar energetic particles (SEPs) that have been produced by solar eruptions. Ground‐level enhancement events are characterized by a significant increase in the count rate of ground‐based neutron monitors (NMs). The arrival of high‐energy SEPs in the atmosphere leads to an enhancement of the radiation environment, with the enhancement at aviation altitudes being particularly hazardous to human health as pilots, crew, and airline passengers can be subjected to dangerous levels of radiation during a GLE. Through the use of a currently expanding library of analyzed GLEs and the application of a newly developed atmospheric radiation model, both of which have been created in‐house, we found a strong statistically significant relationship between real‐time NM data during GLE events and the radiation doses at aviation altitudes. This result provides a strong scientific basis for the use of real‐time NM data as a proxy for radiation dose estimates during GLE events and aids in the development of future nowcasting models to help mitigate the dangerous impacts of future GLEs.